Open vs. closed reduction with pinning for displaced Rockwood and Wilkins' type C thumb metacarpal base fractures in children - Qiao, Fei; Shang, Xinpeng; Jiang, Fei (Frontiers in Pediatrics, 2024)
Background: The treatment of severely displaced Rockwood and Wilkins' type C (RWC) thumb metacarpal basal fractures remains controversial in children. This retrospective study aimed to compare the efficacy of two treatment methods, open versus closed reduction with pinning of such injuries.Methods: This study included 30 patients with open physes, 14 boys and 16 girls, who all received either closed or open reduction treatment. The primary outcomes of interest included healing time, complications, and functional results, which were evaluated using the improved Mayo score standard. The minimum follow-up period was 24 months, with a mean of 30.3 months (range 24.0 to 45.0 months). Statistical significant was defined as P<0.05.Results: All fractures were healed within 7 weeks after surgery, regardless of which surgical approach was used. However, the recovery time was markedly faster in the closed group, with a mean of 4.2 weeks, than in the open group, with a mean of 4.7 weeks (P<0.05). The operation time for closed group, taking 20 minutes in average, was also shorter than that for open group (P<0.05). The total incidence of mild complications was lower for patients in the closed group than for patients in the open group (6.3% vs. 21.4%, P ＜ 0.05). No major complications were observed in either group. In the closed group, a total of fifteen patients exhibited excellent outcomes, while only one patient demonstrated good outcomes. On the other hand, in the open group, twelve patients experienced excellent outcomes, whereas two patients had good outcomes. There were no instances of osteomyelitis, refractures or nonunion, avascular necrosis (AVN), or premature physeal closure in either group.: The data from the open group and closed group procedures for severely shifted RWC fractures in children indicate comparable prognoses and complication rates between the two groups. Obviously closed reduction, in particular, offers several advantages over open procedure, including shorter surgical duration, fewer Kwires required, and no need for open incisions. Consequently, closed reduction is the preferred method for treating such RWC fractures.